The Impact of SSB Independence on the Effectiveness of Internal Shariah Auditor among IFIs in UAE - Alani, Hussein Alwan Dhahir; Khalid Ahmed, Azam Abdelhakeem; Ahmad Zakirullah Mohamed Shaarani (International Business Education Journal, 2023)
This paper aims to examine the impact of Independent of Shariah Supervisory Board (ISSB) on the effectiveness of internal Shariah auditor in Islamic financial institutions (IFIs) in United Arab Emirates (UAE). The research uses a survey questionnaire to collect data from target respondents with a sample size of 100, who are selected using a simple random sampling technique. In developing SEM model and testing the hypothesis, SPSS and AMOS are used to analyse this research. The research utilizes the Islamic accountability theory to provide the foundation in explaining the impact of ISSB on Internal Shariah Auditor Effectiveness (ISAE). The research results indicate the significant positive effects of ISSB on ISAE. The SPSS analysis confirms that the construct is sufficient and capable to construct the model target of the research. The results indicate that the data actually fit the research model, which can represent the structural relations among the research variables in a proper way. This work takes an empirical approach; starting with a comprehensive review of previous literature. In order to meet the effectiveness requirements of ISA, and with reference to the idea of the ISSB, a theory of Islamic accountability is first described and then put into practice. To ensure Shariah compliance by IFIs, the effectiveness of the ISA and its direct relationship with the ISSB must be known. Therefore, the research suggests that the Islamic accountability theory serves as a theoretical basis for building a multi-dimensional conceptual framework that relies on the independence of SSB in evaluating the work, performance, and effectiveness of the ISA. From secondary sources evidence, IFIs need to increase the level of the ISSB to assure the ISAE. This research fills that gap since ISAE in IFIs has not been extensively studied in comparison to both studies of the effectiveness of external Shariah auditors in IFIs, and internal auditors undertaken by conventional financial institutions, respectively.